Decolonizing Literary Studies: Unveiling Postcolonial Narratives in Post-Yugoslav Academic Curricula* - Sara Vukotić; Darko Ilin (Acta Paedagogica Vilnensia)
This paper explores the presence and integration of postcolonial studies in literature education within the faculties of philology in the capitals of the former Yugoslav countries. Focusing on the emerging field of critical curriculum studies, the research delves into the nuanced landscape of literature education, particularly at higher levels, specifically emphasizing literary students’ specialized education. The study contextualizes postcolonial studies as a hybrid space for theoretical discourse, tracing its roots to anticolonial critique and contemporary Western theories. Drawing on the anticolonial heritage of socialist Yugoslavia and its involvement in the Non-Aligned Movement, the paper navigates the complexities of (post)colonial dynamics in the Balkans. This paper investigates the presence, or absence, of postcolonial theory in literature curricula within humanities faculties in the former Yugoslav countries’ capital cities. This research is based on the close interconnection of literature and postcolonial theory, whose origins lie within the literary representation of colonization relations. The primary objective is to discern the extent to which postcolonial studies are integrated into literary education and what implications this holds within the national context. Through an examination of course programs and content at various academic levels, the research aims to illuminate the role of postcolonial theory in shaping the narrative of literature education in the context of the former Yugoslavia.